2002
DOI: 10.1590/s1517-83822002000300009
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Staphylococcus spp. and Candida spp. in the human oral cavity

Abstract: The presence of yeasts and staphylococci in the oral cavity is important because they can act as supplementary microbiota and in certain situations can cause oral or systemic diseases. The aim of this work was to study the prevalence of Candida spp. and Staphylococcus spp. in the human oral cavity. Oral rinses were collected from sixty-eight individuals according to the technique described by Samaranayake and MacFarlane and then cultured on Sabouraud medium supplemented with chloramphenicol and Baird-Parker ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
1
13
0
2
Order By: Relevance
“…Dahlém and Wikström (3) (2,5,8,10,14). S. hycus (17%) and S. scheleiferi subspecies coagulans (6.1%) were also found in the oral cavity in the study of Martins et al (9) in health individuals using methodology similar to collect the oral rinses. Rams et al (14) reported approximately 50% of periodontal lesions harbored subgingival staphylococci.…”
Section: Discussionmentioning
confidence: 90%
“…Dahlém and Wikström (3) (2,5,8,10,14). S. hycus (17%) and S. scheleiferi subspecies coagulans (6.1%) were also found in the oral cavity in the study of Martins et al (9) in health individuals using methodology similar to collect the oral rinses. Rams et al (14) reported approximately 50% of periodontal lesions harbored subgingival staphylococci.…”
Section: Discussionmentioning
confidence: 90%
“…1 These microorganisms are found in the oral cavity of approximately 95% of healthy individuals and have become a matter of concern because of their capacity to develop resistance against antimicrobial agents. 2,3 In addition to their involvement in oral diseases, such as angular cheilitis, parotiditis, staphylococcal mucositis and periodontitis, these bacteria are the causative agents of severe skin and soft tissue infections that are associated with an increased risk of complications, such as bacteremia, pneumonia and endocarditis. 1,[4][5][6][7] Methicillin-resistant Staphylococcus aureus (MRSA) has been isolated from the oral cavity of healthy individuals, a finding that indicates an increased risk of dissemination to other sites.…”
Section: Introductionmentioning
confidence: 99%
“…Species of the Candida genus are frequently isolated from the oral cavity in the majority of healthy individuals (24, 34), living normally in a relationship of commensalism. Nevertheless, these microorganisms can act as opportunist pathogens, invading tissues and setting off infectious processes (10, 23).…”
Section: Introductionmentioning
confidence: 99%